Transnational intergration and national disitegration: Regional underdevelopment and spatial imbalance in Greek society - Evangelinides, Mary (The Greek Review of Social Research, 1980)
An attempt has been made to demonstrate that Greek space is characterised by an inter sectoral, inter regional and intra-regional duality as well as by a highly disintegrated economic structure. The above evidence was used to contest the assumptions of the classical location theories of Weber, Isard, Christaller, Lösch and Alonso, who emphasised the existence of a homogeneous and balanced distribution of physical and human resources in space; and the assumptions of the theory of inter\regional flows of factor movements of Lutz and Richardson, who attributed to these flows virtuous effects in relation to inter regional imbalance. A further conclusion drawn from the historical development of the Greek socio-economic spatial structure was that until 1922 there were no definite national boundaries. Consequently, the conventional disequilibrium models of regional distribution of resources, which tend to abstract national space from the wider international context, would impede identification of the relation between what we have called transnational integration, national and regional disintegration of socio-economic structures in Greece. For such reasons it was claimed that the models of centre-periphery and dependency theories, suggested by Friedmann, Frank, Amin and Sunkel, would prove more relevant for analysing Greek soci» economic space. By employing these models, we have demonstrated that urban and regional polarisation in the modern Greek State was caused by a new system of authority-dependency relations which was grafted onto a pre-capitalist «traditional» system of society, and which radically transformed the spatial organization of the existing urban system. The new national élites, in close partnership with foreign capital, amassed a growing proportion of the nation’s wealth. Moreover, the new import-substitution industrialisation policies implemented by the élites contributed to the growing primacy of the Athens region, where processes of «circular and cumulative causation» sustained accelerated growth. Thus, a vicious circle of cumulative disequilibrium was set in motion, which produced a type of urbanisaton without industrialisation with its concomitant phenomena of «involution» and «ruralisation». The conclusions of our research pointed to a structural heterogeneity that suggests five different levels of technology, organization and social relationships within the major economic sectors of Greece's socio-economic formation.